Quiet FLAIR at 7T MRI - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Dörfler, Arnd; Grodzki, David M. (Investigative Radiology, 2020)
OBJECTIVE: The aim of this study was to investigate acoustic noise reduction and image quality of cranial magnetic resonance imaging (MRI) at 7T MRI with and without sequence-based acoustic noise reduction. MATERIALS AND METHODS: Fifteen patients and 5 healthy volunteers underwent 7T MRI scanning. A fluid-attenuated inversion recovery (FLAIR) sequence was acquired with and without sequence-based acoustic noise reduction. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio, contrast-to-noise ratio, lesion conspicuity, level of artifacts, and overall image quality were performed. Furthermore, detection rates of white matter lesions were evaluated by 2 observers for both sequences. RESULTS: Acoustic noise was significantly reduced from initially 92.7 dB(A) to 78.9 dB(A), corresponding to an 80% reduction in sound pressure. The visual assessment revealed no significant difference in the level of artifacts. Although rated very high by both readers, lesion conspicuity and image quality averaged better for the regular FLAIR sequence. Signal-to-noise ratio and contrast-to-noise ratio slightly decreased when applying the sequence-based acoustic noise reduction. No significant difference was found between the detection rates of white matter lesions for both observers. CONCLUSIONS: Reducing sound pressure by 80% in FLAIR imaging at 7T ultra-high-field MRI is feasible while maintaining high diagnostic image quality.
CRIS-Team Scopus Importer:2020-10-23